Design of training processes in manual order picking - Klaus Möller; Fritz Gairing; Daniel Mezger; Thomas Jehnichen (Hochschule Pforzheim, 2020)
Logistics processes are strongly affected by automation but due to the prevailing conditions the demand for human labor will still remain in intralogistics, in particular in manual order picking. While the results of previous research work on learning processes in manual order picking are mainly available in the form of learning curves, the present research project focuses on the qualitative dimension of these learning processes. Based on current teaching-learning research, suitable learning formats were developed and consolidated as learning packages for practical use. We have considered a variety of learning methods, from enhanced instruction methods common in many companies to the use of modern learning media such as tablets or Virtual Reality. These can be used in companies today and in the future. An extensive study with test persons in a laboratory environment called LernLager (Learning Warehouse) focused on and optimized those learning packages, looking particularly at four different picking technologies: Pick-by-Light, Pick-by-Scan, Pick-by-Voice and Pick-by-Vision. In order to reflect on the results of the test persons' experiments and to prepare transferring the results into practice, hands-on experts subsequently discussed the practicability and transferability of the learning packages in workshops. The results of the research project show that if methodologically and didactically elaborated learning formats are adapted to practical situations and target groups, they can significantly promote the learning process. At the same time, new employees are motivated to play an active role in the learning process and to acquire new knowledge and skills in the long run.
urn:nbn:de:bsz:951-opus-138
Keywords: 330